Image Guidance in Ablation for Hepatocellular Carcinoma: Contrast-Enhanced Ultrasound and Fusion Imaging - Minami, Yasunori; Kudo, Masatoshi (Frontiers in Oncology, 2021)
The ultrasound (US) imaging technology, including contrast-enhanced US (CEUS) and fusion imaging, has experienced radical improvement, and advancement in technology thus overcoming the problem of poor conspicuous hepatocellular carcinoma (HCC). On CEUS, the presence or absence of enhancement distinguishes the viable portion from the ablative necrotic portion. Using volume data of computed tomography (CT) or magnetic resonance imaging (MRI), fusion imaging enhances the three-dimensional relationship between the liver vasculature and HCC. Therefore, CT/MR-US fusion imaging provides synchronous images of CT/MRI with real-time US, and US-US fusion imaging provides synchronous US images before and after ablation. Moreover, US-US overlay fusion can visualize the ablative margin because it focuses the tumor image onto the ablation zone. Consequently, CEUS and fusion imaging are helpful to identify HCC with little conspicuity, and with more confidence, we can perform ablation therapy. CEUS/fusion imaging guidance has improved the clinical effectiveness of ablation therapy in patients with poor conspicuous HCCs. Therefore; this manuscript reviews the status of CEUS/fusion imaging guidance in ablation therapy of poor conspicuous HCC.